Nature-Assembled Structures for Delivery of Bioactive Compounds and Their Potential in Functional Foods - Acevedo-Fani, Alejandra; Dave, Anant; Singh, Harjinder (Frontiers in Chemistry, 2020)
Consumers are demanding more natural, healthy, and high-quality products. The addition of health-promoting substances, such as bioactive compounds, to foods can boost their therapeutic effect. However, the incorporation of bioactive substances into food products involves several technological challenges. They may have low solubility in water or poor stability in the food environment and/or during digestion, resulting in a loss of their therapeutic properties. Over recent years, the encapsulation of bioactive compounds into laboratory-engineered colloidal structures has been successful in overcoming some of these hurdles. However, several nature-assembled colloidal structures could be employed for this purpose and may offer many advantages over laboratory-engineered colloidal structures. For example, the casein micelles and milk fat globules from milk and the oil bodies from seeds were designed by nature to deliver biological material or for storage purposes. These biological functional properties make them good candidates for the encapsulation of bioactive compounds to aid in their addition into foods. This review discusses the structure and biological function of different nature-assembled carriers, preparation/isolation methods, some of the advantages and challenges in their use as bioactive compound delivery systems, and their behavior during digestion.